Physical Therapists in Primary Care Are Interested in High Quality Evidence Regarding Efficacy of Therapeutic Ultrasound for Knee Osteoarthritis: A Provincial Survey - Norma J. MacIntyre; Jason W. Busse; Mohit Bhandari (The Scientific World Journal)
Recent high-level evidence favours therapeutic ultrasound (US) for reducing pain in people with knee osteoarthritis (OA). It is unknown how current practice patterns align with current evidence regarding US efficacy and whether physical therapists perceive a need for further high-level evidence. We conducted a descriptive electronic survey to characterize the beliefs and use of US among physical therapists in Ontario treating people with nonsurgical knee OA. Most of the 123 respondents (81%) reported at least some use of US with 45% using it often or sometimes. The main goal for using US was to reduce pain in the surrounding soft tissue (n=66) and/or the knee joint (n=43). Almost half (46%) endorsed the belief that US is likely to be beneficial for clients with nonsurgical knee OA. Most respondents (85%) expressed interest in the results of a randomized controlled trial evaluating the effectiveness of US on pain and physical function. Patterns of use reflect the respondents’ belief that US is likely to be beneficial for knee OA pain.